Exploring the connection between erythrocyte membrane fatty acid composition and oxidative stress in patients undergoing the Crohn’s disease Therapeutic Diet Intervention (CD-TDI) - Natasha Haskey; Clara Letef; James A. Sousa; Munazza Yousuf; Lorian M. Taylor; Derek M. McKay; Christopher Ma; Subrata Ghosh; Deanna L. Gibson; Maitreyi Raman (Therapeutic Advances in Gastroenterology)
Background: Dietary fatty acids (FA) are crucial to the pathophysiology of inflammatory bowel disease (IBD), influencing systemic and gut inflammatory responses. Dietary FA intake influences the fatty acid profiles of vital cell membranes, which might be a source of inflammatory mediators. Despite their significance, research on dietary FA subtypes and their effects on inflammation and oxidative stress in IBD is limited. Objective: We investigated the association between dietary FA intake, the erythrocyte membrane FA composition (EMFA), and inflammation and oxidative stress markers in patients with mild–moderate luminal Crohn’s Disease (CD) participating in the CD Therapeutic Dietary Intervention (CD-TDI). Design: A cross-sectional analysis was performed on 24 participants (13 CD-TDI, 11 habitual diet controls) from a 13-week randomized controlled trial assessing the efficacy of CD-TDI in inducing clinical and biomarker remission in CD. Methods: EMFA was analyzed using direct-injection gas chromatography, and dietary FA intake was assessed using the ASA 24-h Dietary Assessment Tool ® . Results: The CD-TDI group showed a significant increase in dietary n-3 polyunsaturated fatty acids (PUFA) at Week 13 ( p  = 0.04) compared to no changes in the control group. Participants on the CD-TDI also demonstrated a significant reduction in total fat, saturated fat, and arachidonic acid (AA) ( p  < 0.01). EMFA analysis revealed lower percentages of AA ( p  = 0.03) in the CD-TDI group. Positive correlations were observed between C-reactive protein, fecal calprotectin, and dietary stearic acid ( p  < 0.05). Inverse correlations were found between malondialdehyde (MDA) and the Mediterranean Diet Score ( r  = −0.67) as well as MDA and the intake of whole fruit, legumes, and nuts/seeds ( r  > −0.50). Conclusion: The CD-TDI significantly increased dietary n-3 PUFA intake, reduced pro-inflammatory n-6 PUFA (AA), and improved markers of oxidative stress, supporting its potential in CD management. The cell membrane fatty acid profile might be a therapeutic target in CD. Trial registration: NCT04596566.